Evaluation of the mango and cashew trade in the Municipality of Arara-Paraíba-Brazil (Research, Society and Development, 2020)
In view of the importance of market information on fruit crops, this research aimed at a detailed analysis of the mango and cashew trade in the municipality of Arara-PB with prominence in the main businesses of the city, obtaining relevant information on these tropical fruits. The survey was conducted using a semi-structured questionnaire applied to merchants at 29 points of sale. As for the origin of fruit acquisition, mango obtained a percentage of 75.9% acquired from middlemen and 24.13% from the producer, cashew with 72.2% by middlemen followed by 27.8% by producers. The fruits obtained a higher index for the origin of conventional crops and 62.07% of the merchants reported not knowing the difference between organic / agroecological and conventional crops. Both mangoes showed a shelf loss of 41.4%, while for cashews there was a percentage of 77.2%; as for the demand index of the fruits studied, 65.6% were obtained for urban areas and 34.4% in rural areas. Among the mango varieties that make up the city's commerce, the following stand out: Espada; Keitt; Rosa and Tomy, while cashew of the red variety is the most frequent in the market niches of the municipality studied.